The Role of Leadership in Shaping Social Dynamics within Pesantren Communities - Masnur Putra Halilintar; Lailan Rafiqah (Edu Spectrum: Journal of Multidimensional Education, 2024)
This research aims to explore the role of leadership in shaping the social dynamics within Pesantren (Islamic boarding schools) communities in Indonesia. The central purpose of this study is to understand how leadership structures and practices influence the social cohesion, authority relations, and educational environment in these traditional institutions. Using a library research methodology, the study analyzes various scholarly articles, books, and previous studies related to the leadership in Pesantren, as well as sociological theories on power, authority, and community development. The findings indicate that leadership in Pesantren plays a crucial role in fostering social unity, maintaining discipline, and mediating conflicts. The head of the Pesantren (Kyai) often serves as a central figure whose authority shapes the values, norms, and social behaviors of students and staff. Furthermore, the study highlights the intersection of traditional and modern leadership styles within Pesantren, revealing both challenges and opportunities for transformation in the face of social change. The implications of this research suggest that a more nuanced understanding of leadership in Pesantren can contribute to enhancing social integration, improving educational outcomes, and addressing the needs of modern Muslim communities within Indonesia.